Dose-Dependent Infectivity of Aseptic, Purified, Cryopreserved Plasmodium falciparum 7G8 Sporozoites in Malaria-Naive Adults. (16th August 2019) - Laurens, Matthew B; Berry, Andrea A; Travassos, Mark A; Strauss, Kathy; Adams, Matthew; Shrestha, Biraj; Li, Tao; Eappen, Abraham; Manoj, Anita; Abebe, Yonas; Murshedkar, Tooba; Gunasekera, Anusha; et al.
Abstract: Direct venous inoculation of 3.2 × 10 3 aseptic, purified, cryopreserved, vialed Plasmodium falciparum (Pf) strain NF54 sporozoites, PfSPZ Challenge (NF54), has been used for controlled human malaria infection (CHMI) in the United States, 4 European countries, and 6 African countries. In nonimmune adults, this results in 100% infection rates. We conducted a double-blind, randomized, dose-escalation study to assess the infectivity of the 7G8 clone of Pf (PfSPZ Challenge [7G8]). Results showed dose-dependent infectivity from 43% for 8 × 10 2 PfSPZ to 100% for 4.8 × 10 3 PfSPZ. PfSPZ Challenge (7G8) will allow for more complete assessment by CHMI of antimalarial vaccines and drugs. Abstract : Infectivity of aseptic, cryopreserved, vialed Plasmodium falciparum 7G8 clone sporozoites is dose-dependent and equivalent to standard NF54 strain sporozoites. Vialed sporozoites from field-adapted strains facilitate controlled human malaria infection studies in endemic and nonendemic areas.